Real-time dynamic simulation virtual campus - Alexei Sourin (2008)
This project develops a virtual reality database of NTU campus including naturally looking terrain and roads and textured models of buildings. User is able to walk/fly through the virtual campus. Different visualisation conditions are able to apply such as different time of the day and fog.